Crocetin Attenuates Sepsis-Induced Cardiac Dysfunction via Regulation of Inflammatory Response and Mitochondrial Function - Wang, Yanpeng; Yu, Weiwei; Shi, Chenhui; Hu, Pengfei (Frontiers in Physiology, 2020)
Sepsis-induced systemic inflammation can induce cardiac dysfunction, which can result in heart failure and death. Recently, natural drugs/compounds have received increased attention as therapeutic agents to prevent sepsis-induced cardiac dysfunction. Crocetin (CRO) is a natural compound that has been shown to reduce inflammation and cytotoxicity in cardiac ischemia/reperfusion injury. However, the effects of CRO on sepsis-induced cardiac dysfunction have not been evaluated. In this study, we used lipopolysaccharide (LPS)-induced H9c2 cells as an in vitro model to mimic cardiac sepsis. Crocetin significantly alleviated LPS-induced cytotoxicity, cellular apoptosis, and oxidative stress through increased Bcl-2 activity and PI3K-Akt signaling and suppression of caspase 3 and caspase 9 activities. Furthermore, CRO dramatically decreased the mRNA levels of TNF-α, IL-1, IL-6, and IL-8 via suppression of p65/Keap1 signaling and activation of Nrf2/HO-1/NQO1 signaling. In addition, CRO protected mitochondrial respiration, free fatty acid β-oxidation, and mitochondrial morphology in LPS-induced H9c2 cells. This study showed that CRO attenuated LPS-induced cardiac dysfunction via regulation of the inflammatory response and mitochondrial function and potentially had an effect on sepsis-induced cardiac dysfunction.